Problem Of Professional Pedagogical Training Of Future Pedagogical Staff And Its Scientific-Pedagogical Analysis - Urishov Shakir Mamatalievich (Genius Journals, 2025)
This article talks about the problem of professional pedagogical training of future pedagogical personnel, especially students of pedagogical education, and its scientific and pedagogical analysis. Also, information on the problem of professional pedagogical training of future pedagogical personnel and its scientific-pedagogical analysis is provided
Keywords: innovation; technology; interactive methods